Noise characterization and exposure of indoor sporting events - Cranston, Cory J., author; Brazile, William, advisor; Sandfort, Delvin, committee member; Gotshall, Robert, committee member (Colorado State University. Libraries, 2012)
Noise, as a hazard in the work place, has long been recognized as an issue facing workers. The National Institute for Occupational Safety and Health (NIOSH) recognizes that control of noise is a critical issue facing today's employers and employees. Occupational hearing loss was identified as one of the 21 priority areas for research in the next century. A report from the EPA in 1981 estimates that over 9 million Americans are exposed to occupational noise greater than 85 decibels (dB) and more recent estimates from NIOSH indicate excessive noise exposures upwards of 30 million. Occupational and recreational noise exposures were evaluated at a two sporting arenas hosting hockey games at the collegiate and semi-professional level. Between the two facilities studied, a total of 54 personal noise dosimetry samples were taken over the course of seven home hockey games, three at Venue 1 and four at Venue 2. This included 15 worker personal noise samples and nine fan personal noise samples at Venue 1; and 19 worker personal noise samples and 11 fan personal noise samples at Venue 2. Extensive area monitoring was conducted at each venue to further characterize the stadium noise on a location by location basis. These data are useful in characterizing occupational exposure of indoor arena support staff and may also provide a foundation for future research No workers or fans from either venue were exposed to noise in excess of the Occupational Safety and Health Administration (OSHA) permissible exposure limit of an eight-hour time-weighted average (TWA) of 90 A-weighted decibels (dBA) or the eight-hour TWA action limit of 85 dBA. However, six of 15 (40%) workers and three of nine (33%) fans sampled at Venue 1 were exposed to noise in excess of the American Conference of Governmental Industrial Hygienists (ACGIH) recommended threshold limit value (TLV) of 85dBA. In addition, eleven of 19 (57%) workers and ten of 11 (90%) fans sampled at Venue 2 were exposed to noise in excess of the ACGIH noise TLV. A two-way analysis of variance (ANOVA) was conducted on the personal noise dosimetry data from workers and fans to determine if there were significant differences between noise exposures to workers and fans within and between the venues investigated. At a 95% confidence level, it was determined that there were significant noise exposure differences between nearly all groups in evaluating both OSHA and ACGIH criteria. However, no significant noise exposure differences were detected between workers at the different venues.
Keywords: acoustics; dosimetry; hockey; industrial hygiene; noise; noise exposure